2017
DOI: 10.1016/j.ajpath.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

SPARC Interacts with Actin in Skeletal Muscle in Vitro and in Vivo

Abstract: The cytoskeleton is an integral part of skeletal muscle structure, and reorganization of the cytoskeleton occurs during various modes of remodeling. We previously found that the extracellular matrix protein secreted protein acidic and rich in cysteine (SPARC) is up-regulated and expressed intracellularly in developing muscle, during regeneration and in myopathies, which together suggests that SPARC might serve a specific role within muscle cells. Using co-immunoprecipitation combined with mass spectrometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
3
21
0
1
Order By: Relevance
“…In aggressive tumor phenotypes, SPARC may act as a positive regulator of metastatic potential by augmenting vascular permeability [84]. Persistent induction of SPARC promotes tissue fibrosis, nephropathy, retinopathy, and non-alcoholic fatty liver disease, while its deletion/inhibition protects against the same [8587]. Considering that circulating SPARC is up-regulated in metabolic disease, accelerated aging conditions (Werner Syndrome etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aggressive tumor phenotypes, SPARC may act as a positive regulator of metastatic potential by augmenting vascular permeability [84]. Persistent induction of SPARC promotes tissue fibrosis, nephropathy, retinopathy, and non-alcoholic fatty liver disease, while its deletion/inhibition protects against the same [8587]. Considering that circulating SPARC is up-regulated in metabolic disease, accelerated aging conditions (Werner Syndrome etc.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that circulating SPARC is up-regulated in metabolic disease, accelerated aging conditions (Werner Syndrome etc. ), and in sarcopenia [85, 8893], it is conceivable that it may be used as a general biomarker of advancing age and/or pathological aging processes.…”
Section: Resultsmentioning
confidence: 99%
“…8 ) myoblasts in mice. Recent studies showed that SPARC affects the differentiation of human muscle cells by regulating cytoskeletal remodeling 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Car3 is a muscle-specific carbonic anhydrase 33 . Sparc is a secreted muscle protein 34,35 . Pfkfb3 is transcriptionally regulated via p38 pathway following stress and functions in glycolysis 36,37 .…”
Section: Discussionmentioning
confidence: 99%